Mapping hotspots of tuberculosis cases with validation on site in Gombak, Selangor, Malaysia - Mohidem, Nur Adibah; Osman, Malina; Hashim, Zailina; Muharam, Farrah Melissa; Mohd Elias, Saliza; Ma’pol, Aminuddin (Springer Science and Business Media B.V., 2024)
Tuberculosis (TB) is regarded as one of the leading causes of death globally. The control strategies and resource allocation need to be prioritized in high risk areas by implementing accurate mapping of spatial heterogeneity of the disease. This cross-sectional study aimed to identify the hotspots of TB cases with validation on site in Gombak district, Malaysia. The 3325 cases of TB from 1st January 2013 to 31st December 2017 were collected from the MyTB web and Tuberculosis Information System database. The data includes individual’s ID, date of diagnosis, and patient’s address. The coordinate of each patient’s address was geocoded using Google Earth and then they were georeferenced with the base map of Gombak using geographic information system. Getis-Ord Gi* statistics was used to identify the hotspots of TB cases. The hotspots analysis were validated by capturing pictures of the locations during field visit and compared with the hotspot map. The hotspots of TB cases were consistently distributed at the southwestern part of Gombak, with 99 confidence level that includes 136 points across 5-year period, where the prison was located. Other location of hotspots includes apartments, hostels, markets, factories, and schools. The hotspots shifted gradually from the northwestern to the southwestern parts of the district. This study revealed heterogeneity in the spatial distribution of TB across vulnerable and densely populated areas, thus able to conduct early screening, initiate the treatment, and improve the intervention programme. In the future, inclusion of associated risk factors of the disease based on genotyping of the isolates was recommended to track the TB transmission from different sources to the hotspot’s location.